What works in psychotherapy - Miller, Scott; Wyatt, Randall C. (San Francisco, CA. : Psychotherapy.net, 2009)
Scott Miller and Randall Wyatt discuss factors that contribute to positive and negative outcomes in psychotherapy and conclude that the therapeutic alliance is the most important factor
DVD
Keywords: Psychotherapy